Can routine information systems be used to monitor serious disability?. Issue 1 (1st January 1999) - Johnson, Ann; King, Rosemary
Abstract : OBJECTIVE: To determine whether reliable birth cohort prevalence rates of disabling conditions in early childhood can be obtained from child health information systems. DESIGN: Comparison of two sources of information on motor and sensory disabilities: from child health information systems held by health authorities, and a population register that uses multiple sources of ascertainment. SETTING: The counties of Oxfordshire, Buckinghamshire, and Northamptonshire. PARTICIPANTS: Children born to residents of the three counties between 1984 and 1989. RESULTS: Eight hundred and twenty children (6.0/1000 live births) were identified from the child health system as having one or more of the conditions, and 580 (4.2/1000 live births) were identified from the population register; however, only 284 children were identified by both sources. CONCLUSIONS: It is currently impossible to monitor trends in the prevalence rate of disabling disorders in childhood using the child health information systems. Agreement about ways of collecting, recording, and collating information on disability would be a useful step towards realising the full potential of these systems.